2022
DOI: 10.1186/s12875-022-01821-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pharmacist-led intervention to improve medication adherence in patients initiating dabigatran treatment: a comparison with standard pharmacy practice in Poland

Abstract: Backround Dabigatran is a direct thrombin inhibitor used to treat cardiac arrhythmias, and rates of non-adherence to dabigatran in Polish populations are high. The current study examined how a pharmacist-led intervention of counselling with pictogram-enhanced medication instructions, and smartphone medication reminders, can improve adherence to dabigatran. Methods A 3-month pharmacist-led intervention was conducted in community pharmacies in Poland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A study conducted in the Netherlands showed that both patients and healthcare professionals preferred face-toface consultations over telemedicine for new patients, e.g., hospital discharge patients [60]. Future transfer to virtual care models should explore various telehealth models, e.g., video counselling, which could incorporate the use of tools such as pictograms and smartphone programs, as these have been proven effective in supporting patients' understanding and subsequent medication adherence [61]. The lack of pharmacist face-to-face contact with patients may also have negatively impacted on the prioritisation of patients for medication management services.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the Netherlands showed that both patients and healthcare professionals preferred face-toface consultations over telemedicine for new patients, e.g., hospital discharge patients [60]. Future transfer to virtual care models should explore various telehealth models, e.g., video counselling, which could incorporate the use of tools such as pictograms and smartphone programs, as these have been proven effective in supporting patients' understanding and subsequent medication adherence [61]. The lack of pharmacist face-to-face contact with patients may also have negatively impacted on the prioritisation of patients for medication management services.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a community pharmacist-led intervention using the UK New Medicines Service (NMS) framework was piloted in Poland to see if adherence to dabigatran, previously reported as being suboptimal in 50% of AF patients 133 was improved. 134 The study demonstrated that using a combination of in-person, involving face-to-face (medication reconciliation, patient education, side-effect management); telephone calls (motivational interviewing around adherence challenges and barriers to adherence) and indirect involving pictogram-enhanced information leaflet and medication labels, smartphone daily medication reminders, correlated with better adherence to dabigatran than a control group receiving regular dispensing care. Over 3 months, the study found that patients receiving the intervention were significantly more adherent to their prescribed dose (twice/day) at each time point, than the control group receiving standard care (82.7% vs 71.4% - day 7; 84.4% vs 58% - day 21; 78.4% vs 39.7% - day 90).…”
Section: Pharmacist-led Oac Management Interventionsmentioning
confidence: 95%
“…Numerous studies have shown that pharmacists are willing to extend their services to play a greater role in public health. The NMS has been also implemented in Poland [ 33 , 34 ], where this service was a part of the project “Closer to the Patient”. The findings demonstrated that the use of pharmaceutical intervention in the study group translated into improved adherence to medical instructions regarding correct pharmacotherapy [ 35 ]…”
Section: Challenges To Nms Implementationmentioning
confidence: 99%